Bentuk Komposisi Musik Tradisional Balo-Balo Grup Kampung Tirang Di Kecamatan Tegal Barat Kota Tegal (Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the composition of the traditional music Balo-balo group of Kampung Tirang in Tegal City. The research approach used by the author is descriptive qualitative. The research location is in Murareja Village, West Tegal District, Tegal City. Data collection techniques in this case use observation, interview and documentation techniques. The source of the data that is the focus of the author is the chairman and personnel of the Tirang Village group, who are then analyzed using analysis techniques according to the basic framework that has been prepared. The results of the study indicate that the traditional Balo-balo music of the Kampung Tirang group is an art that uses a pitchbled membranophone musical instrument, namely kencer or tambourine, main drum, kempling, kempyang and gong tambourine. In the lyrics, the group uses the original Tegal language or deles dialect, for example in the song entitled